STUDI SOCIOPRENEURSHIP BUMDES DI KABUPATEN KUNINGAN - Iyan Setiawan, - (2021)
Pada abad 21 masyarakat dan siswa di sekolah harus memiliki kompetensi sociopreneurship dalam menyikapi perilaku ekonomi yang termasuk ruang lingkup bahan pembelajaran IPS. Hanya saja fakta memperlihatkan sociopreneurship di masyarakat terlihat masih rendah. Penelitian ini bertujuan untuk mengeksplorasi dan menyelidiki: 1) pengaruh pelatihan, norma subyektif, sikap kewirausahaan terhadap efikasi diri wirausaha, 2) pengaruh pelatihan, norma subyektif, sikap kewirausahaan, efikasi diri terhadap motivasi wirausaha. 3) pengaruh pelatihan, norma subyektif, sikap kewirausahaan, efikasi diri dan motivasi wirausaha terhadap sociopreneurship. Penelitian ini merupakan jenis penelitian deskriptif dan verifikatif dengan metode penelitian survei. Populasi dalam penelitian ini adalah pengurus/wirausaha sosial bumdes di Kabupaten Kuningan. Teknik pengambilan sampel menggunakan pendekatan total sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner, selanjutnya data yang diperoleh dianalisis menggunakan Partial Least Square-Structural Equationn Modeling (PLS-SEM) Gambaran deskriptif variabel sociopreneurship dari jawaban responden termasuk pada kategori rendah dengan rerata skor item 2.5 (mean) dengan rentang 1.8-2.6. Pelatihan termasuk pada kategori tinggi dari jawaban responden rerata skor item 3.46 (mean) dengan rentang 3.4-4.2. Norma subjektif termasuk pada kategori tinggi rerata skor item 3.43 (mean) dengan rentang 3.4-4.2. Sikap kewirausahaan termasuk pada kategori tinggi rerata skor item 3,57 (mean) dengan rentang 3.4-4.2. Efikasi diri termasuk pada kategori tinggi rerata skor item 3.57 (mean) dengan rentang 3.4-4.2. Selanjutnya motivasi wirausaha termasuk pada kategori kuat rerata skor item 3.60 (mean) dengan rentang 3.4-4.2. Hasil penelitian Model Pemdes menunjukkan sociopreneurship dapat ditingkatkan melalui pengalaman hasil interaksi sumber-sumber belajar disertai pandangan mematuhi harapan orang lain/lingkungannya (aspek sosial) sehingga memediasi efikasi diri dan motivasi dalam meningkatkan sociopreneurship. Hal tersebut sesuai dengan pengembangan kompetensi Pendidikan IPS pada dimensi personal, sosial, dan intelektual agar masyarakat dan siswa di sekolah mampu memahami, menganalisis, dan ikut memecahkan masalah sosial. Berdasarkan temuan tersebut, maka peneliti memberikan rekomendasi:1). bagi pengambil kebijakan penting untuk menerapkan Model Pemdes sehingga dapat meningkatkan kompetensi intelektual, personal dan sosial 2). bagi siswa di sekolah mampu meningkatkan wawasan yang dapat berperan aktif dan berpartisipasi dalam memecahkan masalah sosial3). bagi sekolah dapat dijadikan sebagai solusi dalam meningkatkan kompetensi siswa dalam penguatan karakter, nilai serta jiwa kewirausahaan 4). bagi peneliti selanjutnya dapat menggali pendekatan yang berbeda seperti kualitatif dan Research & Development untuk pengembangan bahan ajar IPS. Kata-kata kunci : Sociopreneurship, Pelatihan, Norma Subyektif, Sikap, Efikasi Diri dan Motivasi Wirausaha ABSTRACT Iyan Setiawan, (2021)."Bumdes Sociopreneurship Study in Kuningan Regency" Dissertation, Social Science Education Study Program. School of Postgraduates, Universitas Pendidikan Indonesia (UPI). Promotor: Prof. Dr. Disman, MS., Copromotor: Prof. Dr. Sapriya, M.Ed., Member: Prof. Dr. Elly Malihah, M.Si. In the 21st century, society and students in schools should have sociopreneurship competence in responding to the economic behavior which is included in social studies learning materials. In fact, sociopreneurship in the community is still low. This study aims to explore and investigate: 1) the effect of training, subjective norms, entrepreneurial attitudes on entrepreneurial self-efficacy, 2) the effect of training, subjective norms, entrepreneurial attitudes, self-efficacy on entrepreneurial motivation. 3) the effect of training, subjective norms, entrepreneurial attitudes, self-efficacy, and entrepreneurial motivation on Bumdes ( village-owned enterprises) sociopreneurship. This research was descriptive and verivicative research with a survey method. The population in this study was the social entrepreneur of Bumdes program in Kuningan Regency. The sampling technique used was a total sampling approach. Data was collected using a questionnaire, then the data obtained were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The descriptive variables of sociopreneurship from the respondents' answers were included in the low category with an average item score of 2.5 (mean) with a range of 1.8-2.6. The training variable was in the high category of respondents' answers with an average item score of 3.46 (mean) with a range of 3.4-4.2. Subjective norm variable belonged to the high category with an average score of 3.43 items (mean) with a range of 3.4-4.2. The entrepreneurial attitude was included in the high category with an average item score of 3.57 (mean) with a range of 3.4-4.2. Self-efficacy was included in the high category with an average item score of 3.57 (mean) with a range of 3.4-4.2. Furthermore, entrepreneurial motivation was in the strong category with an average item score of 3.60 (mean) with a range of 3.4-4.2. The results of Pemdes Model research showed that sociopreneurship can be improved through the experience of learning resource interactions accompanied by the perspective of fulfilling the others' expectation or the environment's expectation (social aspect). As a result, it mediates self-efficacy and motivation in improving sociopreneurship. This is following the character development/competence of Social Science Education that upholds the dimension of personal, social, and intellectual so that the community and students at schools can understand, analyze, and participate in solving social problems. Based on the research findings, the researchers provide the following recommendations: 1) for policymakers, it is important to apply Pemdes Model so that it can improve intellectual, personal and social competence 2) for students at school, it is expected to increase their insights to participate actively in solving social problems in the community 3). for schools, it can be used as a solution in improving students' competence in strengthening character, attitudes, values, and entrepreneurial spirit in strengthening social science learning 4). future researchers are expected to explore deeply about sociopreneurship through different approaches, such as qualitative and research & development approaches for the sake of the development of social science teaching materials. Keywords: Sociopreneurship, Training, Subjective Norms, Attitudes, Self-Efficacy, and Entrepreneurial Motivation